Dialkyl dicyanofumarates and dicyanomaleates as versatile building blocks for synthetic organic chemistry and mechanistic studies - Mlostoń, Grzegorz; Heimgartner, Heinz (Beilstein Journal of Organic Chemistry, 2017)
The scope of applications of dialkyl dicyanofumarates and maleates as highly functionalized electron-deficient dipolarophiles, dienophiles and Michael acceptors is summarized. The importance for the studies on reaction mechanisms of cycloadditions is demonstrated. Multistep reactions with 1,2-diamines and β-aminoalcohols leading to diverse five- and six-membered heterocycles are discussed. Applications of dialkyl dicyanofumarates as oxidizing agents in the syntheses of disulfides and diselenides are described. The reactions with metallocenes leading to charge-transfer complexes with magnetic properties are also presented.
Keywords: cycloaddition reactions; electron-deficient ethenes; heterocyclization reactions; Michael additions; SET mechanism

(untitled) - Fatiadi, A. J. (Synthesis, 1986)

(untitled) - Fatiadi, A. J. (Synthesis, 1987)

(untitled) - Miller, J. S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Felton, D. G. I. (J. Chem. Soc., 1955)

(untitled) - Ireland, C. J.; Jones, K.; Pizey, J. S.; Johnson, S. (Synth. Commun., 1976)

(untitled) - Ali, K. A.; Ragab, E. A.; Mlostoń, G.; Celeda, M.; Linden, A.; Heimgartner, H. (Helv. Chim. Acta, 2013)

(untitled) - Mlostoń, G.; Celeda, M.; Heimgartner, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2016)

(untitled) - Reutenauer, P.; Boul, P. J.; Lehn, J.-M. (Eur. J. Org. Chem., 2009)

(untitled) - Villemin, D.; Alloum, A. B. (Synth. Commun., 1992)

(untitled) - Yamada, Y.; Yasuda, H. (Synthesis, 1990)

(untitled) - Singh, H.; Ahuja, A. S.; Malhotra, N. (J. Chem. Soc., Perkin Trans. 1, 1982)

(untitled) - Kawai, D.; Kawasumi, K.; Miyahara, T.; Hirashita, T.; Araki, S. (Synlett, 2008)

(untitled) - Ioffe, S. L.; Lyapkalo, I. M.; Tishkov, A. A.; Danilenko, V. M.; Strelenko, Y. A.; Tartakovsky, V. A. (Tetrahedron, 1997)

(untitled) - Tamagaki, S.; Tamura, K.; Kozuka, S. (Chem. Lett., 1977)

(untitled) - Tamagaki, S.; Hatamaka, I. (Chem. Lett., 1976)

(untitled) - Cho, L. Y.; Romero, J. R. (Tetrahedron Lett., 1995)

(untitled) - Friedrich, K.; Zimmer, R. (J. Prakt. Chem., 1998)

(untitled) - Mlostoń, G.; Langhals, E.; Huisgen, R. (Tetrahedron Lett., 1989)

(untitled) - Huisgen, R.; Mlostoń, G.; Giera, H.; Langhals, E. (Tetrahedron, 2002)

(untitled) - Gotoh, T.; Padias, A. B.; Hall, H. K. (J. Am. Chem. Soc., 1986)

(untitled) - Sliwinska, A.; Warkentin, J. (Org. Lett., 2007)

(untitled) - Zhou, H.; Mlostoń, G.; Warkentin, J. (Org. Lett., 2005)

(untitled) - Bien, S.; Kapon, M.; Gronowitz, S.; Hörnfeldt, A.-B. (Acta Chem. Scand., Ser. B, 1988)

(untitled) - Huisgen, R.; Mlostoń, G. (Heterocycles, 1990)

(untitled) - Mlostoń, G.; Huisgen, R.; Giera, H. (Tetrahedron, 2002)

(untitled) - Huisgen, R.; Giera, H.; Polborn, K. (Tetrahedron, 2005)

(untitled) - Giera, H.; Huisgen, R.; Langhals, E.; Polborn, K. (Helv. Chim. Acta, 2002)

(untitled) - Huisgen, R.; Mlostoń, G. (Tetrahedron Lett., 1989)

(untitled) - Huisgen, R.; Mitra, A.; Moran, J. R. (Chem. Ber., 1987)

(untitled) - Srisiri, W.; Padias, A. B.; Hall, H. K., Jr (J. Org. Chem., 1994)

(untitled) - Padias, A. B.; Hedrick, S. T.; Hall, H. K., Jr (J. Org. Chem., 1983)

(untitled) - Klarner, F.-G.; Naumann, M. (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Huisgen, R.; Mlostoń, G.; Langhals, E. (J. Am. Chem. Soc., 1986)

(untitled) - Huisgen, R.; Langhals, E.; Mlostoń, G.; Oshima, T.; Rapp, J. (Lect. Heterocycl. Chem., 1987)

1,3-Dipolar Cycloadditions – Beyond Concertedness - Huisgen, R.; Mlostoń, G. (University Press, 2004)

(untitled) - Woźnicka, M.; Rutkowska, M.; Mlostoń, G.; Majchrzak, A.; Heimgartner, H. (Pol. J. Chem., 2006)

(untitled) - Morán, J. R.; Tapia, I.; Alcázar, V. (Tetrahedron, 1990)

(untitled) - Mlostoń, G.; Urbaniak, K.; Domagała, M.; Pfitzner, A.; Zabel, M.; Heimgartner, H. (Helv. Chim. Acta, 2009)

(untitled) - Khlebnikov, A. F.; Konev, A. S.; Virtsev, A. A.; Yufit, D. S.; Mlostoń, G.; Heimgartner, H. (Helv. Chim. Acta, 2014)

(untitled) - Kudo, K.-i. (Bull. Chem. Soc. Jpn., 1962)

(untitled) - Lemieux, V.; Gauthier, S.; Branda, N. R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Hirsch, A. K. H.; Reutenauer, P.; Le Moignan, M.; Ulrich, S.; Boul, P. J.; Harrowfield, J. M.; Jarowski, P. D.; Lehn, J.-M. (Chem. – Eur. J., 2014)

(untitled) - Tian, Y.-K.; Shi, Y.-G.; Yang, Z.-S.; Wang, F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Sustmann, R.; Tappanchai, S.; Bandmann, H. (J. Am. Chem. Soc., 1996)

(untitled) - Sustmann, R.; Rogge, M.; Nüchter, U.; Bandmann, H. (Chem. Ber., 1992)

(untitled) - Sustmann, R.; Lücking, K.; Kopp, G.; Rese, M. (Angew. Chem., Int. Ed. Engl., 1989)

(untitled) - Rese, M.; Dern, M.; Lücking, K.; Sustmann, R. (Liebigs Ann., 1995)

(untitled) - Sustmann, R.; Rogge, M.; Nüchter, U.; Bandmann, H. (Chem. Ber., 1992)

(untitled) - Sustmann, R.; Rogge, M.; Nüchter, U.; Harvey, J. (Chem. Ber., 1992)

(untitled) - Lücking, K.; Rese, M.; Sustmann, R. (Liebigs Ann., 1995)

(untitled) - Ikeda, T.; Ikeda, H.; Takahashi, Y.; Yamada, M.; Mizuno, K.; Tero-Kubota, S.; Yamauchi, S. (J. Am. Chem. Soc., 2008)

(untitled) - Ievlev, M. Y.; Lipin, K. V.; Ershov, O. V.; Tafeenko, V. A.; Nasakin, O. E. (Russ. J. Org. Chem., 2014)

(untitled) - Rappoport, Z.; Ladkani, D. (J. Chem. Soc., Perkin Trans. 1, 1974)

(untitled) - Kudo, K.-i. (Bull. Chem. Soc. Jpn., 1962)

(untitled) - Kudo, K.-i. (Bull. Chem. Soc. Jpn., 1962)

(untitled) - Dell’Erba, C.; Novi, M.; Petrillo, G.; Tavani, C. (Tetrahedron, 1995)

(untitled) - Mlostoń, G.; Celeda, M.; Linden, A.; Heimgartner, H. (Helv. Chim. Acta, 2009)

(untitled) - Mlostoń, G.; Celeda, M.; Linden, A.; Heimgartner, H. (Heterocycles, 2009)

(untitled) - Mlostoń, G.; Heimgartner, H. (Heterocycles, 2010)

(untitled) - Mlostoń, G.; Heimgartner, H. (Helv. Chim. Acta, 2006)

(untitled) - Mlostoń, G.; Pieczonka, A. M.; Ali, K. A.; Linden, A.; Heimgartner, H. (ARKIVOC, 2012)

(untitled) - Mlostoń, G.; Pieczonka, A. M.; Wróblewska, A.; Linden, A.; Heimgartner, H. (Heterocycles, 2012)

(untitled) - Yamada, Y.; Yasuda, H.; Yoshizawa, K. (Heterocycles, 1998)

(untitled) - Abdel-Aziz, M.; Abou-Rahma, G. E.-D. A.; Hassan, A. A. (Eur. J. Med. Chem., 2009)

(untitled) - Hassan, A. A.; Ibrahim, Y. R.; Shawky, A. M. (Z. Naturforsch., 2008)

(untitled) - Hassan, A. A.; Aly, A. A.; El-Sheref, E. M. (J. Chem. Res., 2008)

(untitled) - Yamada, Y.; Yasuda, H.; Kasai, M. (Heterocycles, 1999)

(untitled) - Yamada, Y.; Yasuda, H. (J. Heterocycl. Chem., 1998)

(untitled) - Yamada, Y.; Yasuda, H.; Yoshihara, Y.; Yoshizawa, K. (J. Heterocycl. Chem., 1999)

(untitled) - Hassan, A. A.; Shehata, H. S.; Döpp, D. (J. Chem. Res., 2008)

(untitled) - Mlostoń, G.; Capperucci, A.; Tanini, D.; Hamera-Fałdyga, R.; Heimgartner, H. (Eur. J. Org. Chem., 2017)
accepted.

(untitled) - Kaul, B. B.; Durfee, W. S.; Yee, G. T. (J. Am. Chem. Soc., 1999)

(untitled) - Kaul, B. B.; Sommer, R. D.; Noll, B. C.; Yee, G. T. (Inorg. Chem., 2000)

(untitled) - Tyree, W. S.; Slebodnick, C.; Spencer, M. C.; Wang, G.; Merola, J. S.; Yee, G. T. (Polyhedron, 2005)

(untitled) - Kaul, B. B.; Noll, B. C.; Yee, G. T. (J. Solid State Chem., 2001)

(untitled) - Jones, G., II; Becker, W. G.; Chiang, S. H. (J. Am. Chem. Soc., 1983)

(untitled) - Jones, G., II; Becker, W. G. (J. Am. Chem. Soc., 1983)

(untitled) - Haga, N.; Takayanagi, H.; Tokumaru, K. (Photochem. Photobiol. Sci., 2003)

(untitled) - Linn, W. J.; Webster, O. W.; Benson, R. E. (J. Am. Chem. Soc., 1965)

(untitled) - Achmatowicz, O., Jr; Szymoniak, J. (Tetrahedron, 1982)

(untitled) - Ushkov, A. V.; Kuznetsov, M. A.; Linden, A.; Heimgartner, H. (Helv. Chim. Acta, 2010)